Seeking for sustainability : actor’s perspective on the Malaysian Sustainable Palm Oil Certification Scheme (MSPO) - Siti Rahyla Rahmat,; Suziana Mat Yasin,; Mohamad Fadhli Mad’ Atari,; Azmil Tayeb, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Malaysian government established the Malaysian Sustainable Palm Oil (MSPO) certification primarily as a response to critics against the Roundtable on Sustainable Palm Oil (RSPO), chief among which is to urge the Malaysian government to play a more proactive role in protecting local palm oil producers. The aim of this study is threefold: (1) to identify why the Malaysian government creates MSPO; (2) to understand how Malaysian actors push for the MSPO; and (3) to investigate the current state of MSPO. We conducted nine expert interviews and four in-depth interviews with oil palm small holders. The study finds that the policy regarding palm oil in Malaysia is predominantly top-down in nature. The study concludes that the establishment and implementation of local palm oil certification standard as an alternative to the RSPO is not as straight-forward and more awareness among the smallholders on the importance of getting certified by MSPO is crucial. MSPO may establish a more effective and clearer line of communication between the federal government and the oil palm producers at the local level specifically small holders. The federal government, state agencies and MPOB needs to create awareness among the smallholders on the importance of getting certified by MSPO.